Developing biocultural indicators for resource management. Issue 6 (30th April 2019) - Dacks, Rachel; Ticktin, Tamara; Mawyer, Alexander; Caillon, Sophie; Claudet, Joachim; Fabre, Pauline; Jupiter, Stacy D.; McCarter, Joe; Mejia, Manuel; Pascua, Pua'ala; Sterling, Eleanor; Wongbusarakum, Supin
Abstract: Resource management and conservation interventions are increasingly embracing social–ecological systems (SES) concepts. While SES frameworks recognize the connectedness of humans and nature, many fail to acknowledge the complex role of sociocultural factors in influencing people's interactions with the environment. As such, when indicators in SES frameworks are used to measure the social dimension, easy to measure, socioeconomic indicators are the norms, while more complex social and cultural indicators are rare. To develop meaningful indicators of resilience in SES we need to understand local definitions of resilience. In this paper we describe methods used in a biocultural approach to illuminate sociocultural factors that Pacific Islanders identify as important for resilient communities. We focus specifically on two dimensions of sociocultural factors, "Connectedness to People and Place" and "Indigenous and local knowledges, skills, practices, values and worldviews, " which relate to many interventions, but are not usually monitored. We offer examples of indicators that may be appropriate to measure under these dimensions. Increased use of biocultural indicators will bring additional insight on the types and combinations of indicators that work best in given contexts.